Alligator Abundance and Hydrology (2003–2013): What Long-term Monitoring Can Tell Us about Everglades Restoration - Rebecca G. Harvey; Jeff Beauchamp; Robin Bijlani; Frank J. Mazzotti; Laura A. Brandt (EDIS, 2014)
The American alligator is a powerful indicator for Everglades restoration. It responds clearly to environmental change and is easy and inexpensive to monitor. As top predators and ecological “engineers,” alligators affect nearly all aquatic life in the ecosystem. Thus, trends in alligator populations can tell us whether restoration projects are successful. Alligators may be monitored for both short-term responses (body condition) and longer-term responses to ecosystem change (abundance). This 3-page fact sheet discusses trends in alligator abundance. It was written by Rebecca G. Harvey, Jeff Beauchamp, Robin Bijlani, Frank J. Mazzotti, and Laura A. Brandt, and published by the UF Department of Wildlife Ecology and Conservation, July 2014.